2018
DOI: 10.18203/2320-1770.ijrcog20184503
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis on acceptability and complications of PPIUCD insertion

Abstract: Background: In India, 65% of women in the first year postpartum have an unmet need for family planning but only 26% of women are using any method of family planning during the first year postpartum. This leaves a huge gap which needs to be addressed if maternal health is to be optimized. This calls for a method which is both effective and acceptable immediately post-partum. This is where the role of PPIUCD needs to be studied.Methods: This study was a retrospective observational study conducted in a tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…One-third of maternal mortality and 10% of child mortality can be decreased if the spacing between the two pregnancies is more than 2 years 1 and PPIUCD is the way to go for achieving spacing in a reversible fashion. Women preferred this method due to sufficiently long duration 4,13,16,18,19,26 of action for meant for spacing between births as per some studies. Many studies suggested that women being motivated and being aware with the use of proper counselling was a major reason for acceptance of this method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One-third of maternal mortality and 10% of child mortality can be decreased if the spacing between the two pregnancies is more than 2 years 1 and PPIUCD is the way to go for achieving spacing in a reversible fashion. Women preferred this method due to sufficiently long duration 4,13,16,18,19,26 of action for meant for spacing between births as per some studies. Many studies suggested that women being motivated and being aware with the use of proper counselling was a major reason for acceptance of this method.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested that women being motivated and being aware with the use of proper counselling was a major reason for acceptance of this method. [4][5][6][7][8][9][10][11][12][13][14]28 A few other studies showed that women were more accepting of this method because of its safety and efficacy, 7,[13][14][15][16][17][18][19][20][21][22] and some preferred it due to availability of trained service providers. 6,11,12,23 In this study, women who were currently using PPIUCD were satisfied with the method due to its safety, efficacy, reversibility, husband's approval, long duration of action, awareness, incentivization and proper training to ASHAs/ANMs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies have recorded rates as low as 8% to as high as 50%. [14][15][16][17][18] A low acceptance rate (8.2%) has been recorded by Prabha et al 14 In a study conducted by Kachan Rani, 15 high rate (51.6%) of acceptance of PPIUCD was found. An acceptance rate ranging between 43.8 -50% has been mentioned in a research work done by Rajuan Doley et al 18 The rate (24.36%) of PPIUCD insertion recorded in our study lies midway between above mentioned studies.…”
Section: Discussionmentioning
confidence: 89%